Long term management of patients with cryopyrin-associated periodic syndromes (CAPS): focus on rilonacept (IL-1 Trap) - Leigh D Church (Dove Medical Press, 2008)
Leigh D Church1, Sinisa Savic2, Michael F McDermott21Department of Rheumatology, Division of Immunity, Infection and Inflammation, Institute for Biomedical Research, The University of Birmingham, Birmingham, UK; 2Section of Musculoskeletal Disease, Leeds Institute of Molecular Medicine, Wellcome Trust Brenner Building, University of Leeds, Leeds, UKAbstract: Cryopyrin-associated periodic syndromes (CAPS) are a group of inherited inflammatory disorders consisting of familial cold-induced autoinflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS), and neonatal-onset multisystem inflammatory disease (NOMID; also known as chronic infantile neurologic, cutaneous, articular [CINCA] syndrome). These rare disorders are associated with heterozygous mutations in the NLRP3 (CIAS1) gene, which encodes the protein NALP3 or cryopyrin, and inflammation driven by excessive production of the cytokine interleukin-1β (IL-1β). Amyloidosis is a serious complication with 25% of MWS patients developing amyloidosis, with occasional fatal consequences, whilst up to 20% of CINCA/NOMID patients die from various complications, before reaching the early adulthood. In some CINCA/NOMID adult survivors amyloidosis can also occur. Prior to the discovery of the CIAS1 gene mutations and the advent of IL-1 targeted therapy, treatment was aimed at suppressing inflammation, with limited success. The selective blockade of IL-1β, with anakinra (IL-1 receptor antagonist), not only provided supportive evidence for the role of IL-1β in CAPS, but also demonstrated the efficacy of targeting IL-1β for treatment of these conditions. In February, 2008, ‘Orphan Drug’ approval from the Food and Drug Administration (FDA) for rilonacept (IL-1 Trap/Arcalyst™, Regeneron Pharmaceuticals, Inc) was given for the treatment of two CAPS disorders, FCAS and MWS in adults and children 12 years and older, making rilonacept the first therapy approved for the treatment of CAPS.Keywords: cryopyrin-associated periodic syndromes, interleukin-1, therapy, rilonacept